2018
DOI: 10.1111/jnc.14267
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2‐dependent hyperglycolysis driving microglial activation contributes to ischemic brain injury

Abstract: Hyperglycolysis, observed within the penumbra zone during brain ischemia, was shown to be detrimental for tissue survival because of lactate accumulation and reactive oxygen species overproduction in clinical and experimental settings. Recently, mounting evidence suggests that glycolytic reprogramming and induced metabolic enzymes can fuel the activation of peripheral immune cells. However, the possible roles and details regarding hyperglycolysis in neuroinflammation during ischemia are relatively poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 48 publications
0
67
0
Order By: Relevance
“…Additionally, in our study, for the first time, we demonstrated that not only murine, but also human microglia-like cells exhibit increased glycolysis in a pro-inflammatory setting, implying glycolysis as an M1 microglia feature. Importantly, several studies have already demonstrated that inhibition of glycolysis in microglia can prevent pro-inflammatory microglia activation both in vitro and in vivo, further supporting this notion [31,59,60]. For example, treatment of microglia with 2-deoxyglucose, a glycolytic inhibitor, is able to diminish the NO production in LPS-treated microglia, which could be useful for inhibiting neurotoxic microglia properties [59].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Additionally, in our study, for the first time, we demonstrated that not only murine, but also human microglia-like cells exhibit increased glycolysis in a pro-inflammatory setting, implying glycolysis as an M1 microglia feature. Importantly, several studies have already demonstrated that inhibition of glycolysis in microglia can prevent pro-inflammatory microglia activation both in vitro and in vivo, further supporting this notion [31,59,60]. For example, treatment of microglia with 2-deoxyglucose, a glycolytic inhibitor, is able to diminish the NO production in LPS-treated microglia, which could be useful for inhibiting neurotoxic microglia properties [59].…”
Section: Discussionmentioning
confidence: 84%
“…For example, treatment of microglia with 2-deoxyglucose, a glycolytic inhibitor, is able to diminish the NO production in LPS-treated microglia, which could be useful for inhibiting neurotoxic microglia properties [59]. Moreover, several studies have reported beneficial effects of 2-deoxyglucose in Alzheimer's disease (AD) [34], Parkinson's disease [35], epilepsy [36] and ischemic stroke [31]. However, all these studies involved systemic, nonmicroglia specific treatments, so the effect of such approaches could not be assigned directly or solely to microglia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIF1 and related hypoxia-activated HIF2, however, also induce expression and activity of downstream glycolytic enzymes -PFK-muscle type (PFK-M), regulatory enzymes 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 and -4, aldolase, triosephosphate isomerase (TPI), and GA3PD [38]. This suggests that, unlike in glycolytic overload where only HK2 activity is increased, in hypoxia the flux of glucose metabolism may increase without an increase in G6P and other glycolytic intermediates because of a coordinated increased onward rate of metabolism of glycolytic intermediates [41,42]. A remaining potentially insidious effect, however, is the down regulation of glyoxalase (Glo)1 in hypoxia [43,44] the major enzyme that metabolizes and detoxifies MG [45].…”
Section: Increased Hk2 In Hypoxia May Not Produce Glycolytic Overloadmentioning
confidence: 99%